2015
DOI: 10.1007/s00018-015-1845-y
|View full text |Cite
|
Sign up to set email alerts
|

Platelet–neutrophil interactions under thromboinflammatory conditions

Abstract: Platelets primarily mediate hemostasis and thrombosis, whereas leukocytes are responsible for immune responses. Since platelets interact with leukocytes at the site of vascular injury, thrombosis and vascular inflammation are closely intertwined and occur consecutively. Recent studies using real-time imaging technology demonstrated that platelet–neutrophil interactions on the activated endothelium are an important determinant of microvascular occlusion during thromboinflammatory disease in which inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 225 publications
2
71
1
1
Order By: Relevance
“…Consistent with previous reports showing that the activation and adhesive function of platelets is regulated by AKT, [17][18][19]36 we found that ARQ 092 significantly impairs P-selectin exposure and GPIbα-mediated agglutination in platelets from SCD patients in vitro and in SCD mouse platelets ex vivo. In support of the importance of neutrophil αMb2 integrin and platelet P-selectin and GPIbα for neutrophil-platelet interactions, 13 we observed that specific AKT inhibition in both neutrophils and platelets isolated from SCD patients effectively decreases heterotypic cell-cell aggregation. Thus, our results suggest that co-administration of hydroxyurea and ARQ 092 is beneficial to inhibit cell-cell interactions during vaso-occlusion in SCD.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Consistent with previous reports showing that the activation and adhesive function of platelets is regulated by AKT, [17][18][19]36 we found that ARQ 092 significantly impairs P-selectin exposure and GPIbα-mediated agglutination in platelets from SCD patients in vitro and in SCD mouse platelets ex vivo. In support of the importance of neutrophil αMb2 integrin and platelet P-selectin and GPIbα for neutrophil-platelet interactions, 13 we observed that specific AKT inhibition in both neutrophils and platelets isolated from SCD patients effectively decreases heterotypic cell-cell aggregation. Thus, our results suggest that co-administration of hydroxyurea and ARQ 092 is beneficial to inhibit cell-cell interactions during vaso-occlusion in SCD.…”
Section: Discussionsupporting
confidence: 72%
“…13 Since ARQ 092 inhibited the function of surface molecules on neutrophils and platelets isolated from SCD patients, we investigated whether ARQ 092 affects heterotypic cell-cell aggregation in vitro. Neutrophils and platelets isolated from SCD patients aggregated under stirring conditions mimicking venous shear, creating a new cell population (R1 gate) in which most cells were positive for both L-selectin (a leukocyte marker) and CD41a (αIIb, a platelet marker) ( Figure 2A).…”
Section: Arq 092 Attenuates Heterotypic Aggregation Of Sickle Cell Pamentioning
confidence: 99%
See 1 more Smart Citation
“…For further information, we refer to previous review articles [100,101]. Danger-associated molecular patterns (DAMPs) such as ATP or uric acid can be released from dying stromal cells and can trigger neutrophil migration/activation [103].…”
Section: The Role Of Platelets and Stromal Cells In The Amplificationmentioning
confidence: 99%
“…12 Intravital microscopic studies showed that neutrophil-platelet interactions on activated ECs are the major determinant of vascular occlusion during thromboinflammatory diseases in which inflammation is coupled to thrombosis. 5,13,14 Although the mechanisms mediating neutrophil-platelet interactions remain poorly understood, previous studies showed that platelet and neutrophil AKT2 play critical roles in regulating platelet P-selectin exposure and activation of b 2 integrins, 5,15 thereby mediating neutrophil-EC and neutrophil-platelet interactions under inflammatory conditions. Importantly, we found that basal levels of AKT phosphorylation are significantly increased in neutrophils and platelets isolated from SCD patients compared with those in healthy donors and that short-term treatment with Akti XII, an AKT2-specific inhibitor, reduces neutrophil adhesion and platelet-neutrophil aggregation in venules of Berkeley mice, resulting in improved blood flow rates.…”
Section: Introductionmentioning
confidence: 99%